2006
DOI: 10.1001/archotol.132.9.941
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors for Hearing Loss in Children With Bacterial Meningitis

Abstract: To identify clinical risk factors that predict a higher incidence of hearing loss in children with bacterial meningitis, to determine the overall incidence of hearing loss in a large group of children proven by culture findings to have bacterial meningitis, and to compare clinical characteristics among patients with Streptococcus pneumoniae meningitis and Neisseria meningitidis meningitis. Design: Retrospective review Setting: Tertiary pediatric hospital. Patients: A total of 171 children identified with bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 9 publications
6
39
0
1
Order By: Relevance
“…This was therefore greater than findings of previous studies. Walter et al reported an incidence of 14% [9] consistent with other reports [2,4,10,11]. This is likely due to several factors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This was therefore greater than findings of previous studies. Walter et al reported an incidence of 14% [9] consistent with other reports [2,4,10,11]. This is likely due to several factors.…”
Section: Discussionsupporting
confidence: 73%
“…There were no differences in the prevalence of hearing loss between the two groups. Walter et al showed that being male was a significant independent risk factor for hearing loss [9]. Early age at illness was identified by Grimwood et al as a significant risk factor for hearing loss, with children suffering meningitis before twelve months of age performing more poorly than children suffering meningitis later in infancy and childhood, and age-matched controls, on measures of language and reading skills [12].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of meningitis induced hearing loss is different for varying causative agents such as S. pneumoniae (31–36%), N. meningitidis (8–11%) and H. influenza (6–11%) [13]. Meningitis induced hearing loss is probably the result of the spread of infection to the inner ear via the cochlear aqueduct or modiolus and develops at an early stage of meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial meningitis is the most common cause for acquired hearing loss, with 5%-35% of patients developing permanent SNHL and profound bilateral deafness occurring in up to 4% of patients. 15 Bacterial meningitis often involves a multifactorial mechanism for hearing loss, including labyrinthine involvement, cochlear neuroepithelial damage, and vascular insult. 15 In addition to bacterial meningitis, labyrinthitis can also cause an acquired form of SNHL.…”
Section: Pathology Of the Inner Earmentioning
confidence: 99%
“…15 Bacterial meningitis often involves a multifactorial mechanism for hearing loss, including labyrinthine involvement, cochlear neuroepithelial damage, and vascular insult. 15 In addition to bacterial meningitis, labyrinthitis can also cause an acquired form of SNHL. Viral sources of labyrinthitis are the most common cause and present with sudden hearing loss, vertigo, or tinnitus.…”
Section: Pathology Of the Inner Earmentioning
confidence: 99%